Analytical Study of Soybean Value Chain: The Perspective of Sissala East District in Ghana - James Abagna Azanlerigu; Joseph Kinansua Laary; Hilda Abambire (Archives of Current Research International, 2017)
This study was carried out to assess the soybean value chain and its contribution to household food security in the Sissala East District of the Upper West Region of Ghana. The study critically examined the prospects and challenges of the soybeans value chain to household food security. A case study approach was adopted as a research design, involving random sample of one hundred and ten (110) farmers and purposive sample of ten (10) value chain actors. Self-administered-questionnaire was used as data collection instrument to solicit views from the farmers whilst interview guide was used to obtain information from the value chain actors. The results showed that the introduction of value chain approach in the district has been beneficial to the farmers with increased average farm acreages and seed yields from 5 to 11 maxi bags per acre; and improved linkages and access to soybean markets and processors. The soybean value chain however had some challenges such as untimely delivery of inputs, exploitation of farmers in the chain, high production cost, among others. To sustain the gains made through the interventions, there is the need for heightened collaboration between district assemblies, development partners, farmers and other relevant value chain actors. The policy makers also need to enact bylaws that could regulate the activities of middlemen in order to curtail the exploitation of farmers and other value chain actors. There is the need for government to subsidize agricultural inputs to reduce production cost and improve soybean productivity for enhanced household food security in the district.